Evaluation of in vitro Antioxidant Activity of the Methanolic Extract of the Leaves of Mikania micrantha Kunth. - Kumar Sharma, Hemanta; Mishra, Sushma; Kumar, Atul (Asian Journal of Chemistry, 2011)
Free radicals and reactive oxygen species (ROS) are well known inducer of cellular tissue pathogenesis leading to numerous human diseases such as cancer, inflammatory disorder as well as in aging process. Antioxidants are the compounds which prevent the oxidative damage caused by free radicals and hence ward off the occurrence of the disease, cancer and aging. In present study the free radical scavenging activity of methanolic extract of the leaves of Mikania micrantha Kunth. was carried out using five in vitro methods such as, DPPH scavenging activity, reducing power, nitric oxide scavenging activity, super oxide anion scavenging activity and hydrogen peroxide scavenging activity. The extract showed maximum activity in DPPH method. The result showed that the plant have antioxidant activity.